(untitled) (Research, Society and Development, 2022)
The challenges of teaching school geography are not limited to the recurring situations of lack of: structure in public schools, teacher training or student interest. A counterpoint is necessary to select the right contents that meet the local reality, in addition, that highlight the roots of the community, its relationship to the environment and the conservation of natural resources. Enabling the teaching of school geography through spatial observation and obtaining citizen training inside and outside the school is essential to avoid standardization of content and the low rate of use of the subject. Our work has the general objective of understanding the perception of high school students at E.E.E.F.M. Francisco Ernesto do Rêgo on the Lagoa da Serra, located in the municipality in the city of Queimadas-PB. For the development of this study, we used as methodological aspects the types of bibliographic, descriptive, exploratory and qualitative research on the theme described above, considering School Geography, Environmental Education and Conservation of Natural Resources as themes. To assess the students’ level of perception, a qualitative questionnaire is applied with the following topics on: historicity, possible environmental impacts, conservation measures, community/environment relationship and potential tours of the basin studied. Along with this, we sought to discuss, from several authors, the reality of teaching school geography, environmental education and the daily conflicts of content and didactics and, in addition, the counterpoints of academic geography to school geography. After applying the questionnaires and tabulating the data, the results showed that most of the students interviewed did not know Lagoa da Serra, nor did they know its importance for the municipality.